Elevated temperatures increase chlorpyrifos toxicity in nile tilapia (Oreochromis niloticus) larvae - Badratun Nafis; Firdus Firdus; Muhammad Nasir; Ilham Zulfahmi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Global warming and the extensive use of chlorpyrifos pose serious threats to the hatching success, growth, and survival of Nile tilapia larvae (Oreochromis niloticus). This study aimed to evaluate the combined effect of chlorpyrifos toxicity and elevated temperatures on tilapia larvae. A completely randomized design (CRD) was used with three temperature levels (28C, 31C, and 34C) and two chlorpyrifos concentrations (0 g/L and 32 g/L), totaling six treatments with three replicates each. Parameters observed included hatching rate, daily growth rate (DGR), specific growth rate (SGR), absolute growth rate (AGR), and malformation rate.Measurements were conducted daily from the first day of hatching until the end of the larval phase (Day 8). Results showed the highest hatching rate (85.33%) was achieved at 34C without chlorpyrifos, while the lowest rate (20%) occurred at 28C with chlorpyrifos exposure on Day 2. DGR and SGR significantly decreased at 34C with chlorpyrifos exposure, reaching 0.0003 g/day and 3.73%/day, respectively, compared to 28C without chlorpyrifos (0.0011 g/day and 10.78%/day). AGR remained stable across all temperatures, showing no significant differences with or without chlorpyrifos. The malformation rate, including abnormalities such as lordosis and kyphosis, increased with higher temperatures and chlorpyrifos exposure, with the highest rate (25%) recorded at 34C with 32 g/L chlorpyrifosKeywords:ChlorpyrifosNile TilapiaHatching RateLarval Growth